PELATIHAN PERTOLONGAN PERTAMA KASUS TENGGELAM PADA SISWA DI SMAN 1 PLEMAHAN KEDIRI - Ratna Hidayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Drowning is a case of an accident while in the water, consciously while swimming, or an indirect result such as the victim being drunk or under the influence of drugs. Drowning poses a risk of respiratory problems, thus requiring basic life support (BHD) which is a series of rescue measures to maintain life before getting further medical help. By providing first aid training in drowning cases to high school students, it is hoped that they will be able to help and disseminate this information to their friends, family and the wider community. The method of implementing this activity is a problem-based learning method and skill demonstration. The target of this activity is 36 students of SMAN Plemahan, Kediri Regency. The results of this community service have succeeded in increasing knowledge which previously lacked knowledge level of 55.55%, sufficient 27.78%, good 16.67% to less knowledge level 13.89%, sufficient 30.56%, good 55.5%. Meanwhile, psychomotor abilities also increased to sufficient category as much as 30.56% and good as much as 55.55%, which means that more than half of the participants had good psychomotor abilities in demonstrating first aid in drowning cases. The benefits of this activity are expected to be able to disseminate information to their respective families so that the scope of the community who understands first aid for drowning cases becomes wider.